Syntaxin1A-mediated Resistance and Hypersensitivity to Isoflurane in Drosophila melanogaster. (May 2015) - Zalucki, Oressia H.; Menon, Hareesh; Kottler, Benjamin; Faville, Richard; Day, Rebecca; Bademosi, Adekunle T.; Lavidis, Nickolas; Karunanithi, Shanker; van Swinderen, Bruno
Abstract : Background: Recent evidence suggests that general anesthetics activate endogenous sleep pathways, yet this mechanism cannot explain the entirety of general anesthesia. General anesthetics could disrupt synaptic release processes, as previous work in Caenorhabditis elegans and in vitro cell preparations suggested a role for the soluble NSF attachment protein receptor protein, syntaxin1A, in mediating resistance to several general anesthetics. The authors questioned whether the syntaxin1A-mediated effects found in these reductionist systems reflected a common anesthetic mechanism distinct from sleep-related processes. Methods: Using the fruit fly model, Drosophila melanogaster, the authors investigated the relevance of syntaxin1A manipulations to general anesthesia. The authors used different behavioral and electrophysiological endpoints to test the effect of syntaxin1A mutations on sensitivity to isoflurane. Results: The authors found two syntaxin1A mutations that confer opposite general anesthesia phenotypes: syxH3-C, a 14-amino acid deletion mutant, is resistant to isoflurane (n = 40 flies), and syxKARRAA, a strain with two amino acid substitutions, is hypersensitive to the drug (n = 40 flies). Crucially, these opposing effects are maintained across different behavioral endpoints and life stages. The authors determined the isoflurane sensitivity of syxH3-C at the larval neuromuscular junction to assess effects on synaptic release. The authors find that although isoflurane slightly attenuates synaptic release in wild-type animals (n = 8), syxH3-C preserves synaptic release in the presence of isoflurane (n = 8). Conclusion: The study results are evidence that volatile general anesthetics target synaptic release mechanisms; in addition to first activating sleep pathways, a major consequence of these drugs may be to decrease the efficacy of neurotransmission. Abstract : Isoflurane targets synaptic release mechanisms in addition to sleep pathways in flies. Different mutations in syntaxin1A confer resistance and hypersensitivity across multiple behavioral and electrophysiological endpoints in flies.Supplemental Digital Content is available in the text.